Treatment And Prevention Of Uterine Fibroids In Women Of Reproductive Age (Texas Journal of Medical Science, 2025)
In this article we are talking about the female reproductive system - this is a complex network, and in particular about the disease of uterine fibroids, including the uterus and other reproductive organs of women, which is responsible for the reproductive function of the body , and then goes on about the means of promoting the health and healthy lifestyle of women, regular sports and physical exercise, proper nutrition, stress control, regular gynecological examinations, conducting seminars and trainings promoting a healthy lifestyle